Inclusione attraverso le discipline: il caso della Chimica - Aquilini, Eleonora (Chimica nella Scuola, 2025)
In recent years, schools have become familiar with acronyms that categorise the case history of disadvantage. Without detracting from the recognition that certain functional characteristics of individuals exert on learning, one observes an excessive categorisation of forms of hardship that proves paralysing for the educational action of curricular teachers. A dangerous drift of medicalisation of all forms of discomfort is noted, in view of an ideal state of well-being that in reality does not exist. In fact, there is instead a continuum between so-called “normality” and the most serious forms of malaise. The impression is that the concept of inclusion, which should characterise everyday schooling, is fragmenting into bureaucratic classifications followed by pedagogical interventions entrusted to non-experts in the discipline.